Model Pertanggung Jawaban Pidana Korporasi Dalam Sistem Hukum Indonesia - Ragil, Ragil Surya Prakasa; chicha, chichaidiaroza; ihsan, ihsanul adli; Iqbal , Iqbal Achmad Fahrezi; Annisa, Annisa Rahmadani (PUAN INDONESIA, 2024)
In the Indonesian legal system, the corporate criminal liability model is a concept that continues to develop to address corporate activities that have the potential to harm society and the state. This model includes a direct approach (direct responsibility) which places corporations as legal subjects who can determine criminal sanctions for their own actions, as well as an indirect approach (vicarious responsibility) which assigns corporate criminal responsibility to the actions of individuals who represent or act in the interests of the corporation. The implementation of corporate criminal liability in Indonesia is regulated in various sectoral laws, such as Law no. 32 of 2009 concerning Environmental Protection and Management, Law no. 31 of 1999 concerning Eradication of Corruption Crimes, and Law no. 8 of 2010 concerning Prevention and Eradication of Money Laundering. However, the implementation of corporate criminal responsibility still faces various challenges, including evidentiary problems, limitations in law enforcement, and varying legal interpretations among law enforcement officials. Therefore, continued efforts are needed to strengthen the legal framework and increase law enforcement capacity to ensure that corporations can bear responsibility for criminal acts committed.